APPLICATION OF THE FINALE-2003 PROGRAM IN VOCAL AND CHORAL EDUCATION (Scientific journal of the Fergana State University, 2024)
This article analyzes the use of electronic versions of musical works in the process of vocal and choral education in order to improve the quality of vocal and choral education, sound and visual tests made on the basis of the music editor Finale 2003, the use of samples in the educational process, and the independent work of students in the specialty home, about increasing the effectiveness of music education, about preparing visual tests, sound tests. Recommendations are given for using the program in the process of vocal and choral education.